GAMBARAN PERSEDIAAN OBAT DI APOTEK NIAS MEDIKA DENGAN ANALISIS ABC BERDASARKAN RESEP MASUK PERIODE JANUARI-MEI 2020 - Nofrika, Vonny; Agustina, Ika; Priyanti, Risca (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
Pharmacy is a pharmaceutical service facility where pharmacy practices are carried out by pharmacists, namely manufacturing including quality control of pharmaceutical preparations, security, procurement, storage and distribution or distribution of drugs, drug management, prescription drug services, drug information services, and drug development services, drug ingredients and traditional medicine One of the scopes in the management of health services is logistics management, which is a field of management whose specific task is to deal with logistics. Pharmacy nias medika there was no specific arrangement for the procurement of drugs with certain methods so that often there is a vacuum of medicine one of which is for drugs contained in a doctor's prescription that goes to the nias medika pharmacy. For this reason, it was necessary to control drug inventory using certain methods, one of which was by using ABC analysis. The type of research was descriptive and quantitative, based on the prescription entry by recording the name of the drug, the number of drugs, and the unit price of the drug and then processed using data analysis during January-May 2020. The results showed that there were 160 types of drugs based on prescription entry into the drugstore nias medika. With 32 types (20% ) drugs classified as group A with an investment value of 69.68% with laroton drugs which are in the highest position 47 types (29.37%) drugs classified as group B with an investment value of 20.25%, while 81 types (50, 63%) the drugs belong to group C with a total investment of 10.07%.